2023
DOI: 10.1186/s43066-023-00267-7
|View full text |Cite
|
Sign up to set email alerts
|

Absolute eosinophil count is a reliable prognostic marker in patients with liver cirrhosis: a cross-sectional study at rural central India

Abstract: Background Various laboratory parameters like C-reactive protein (CRP), Cortisol, and Von Willebrand factor antigen have been evaluated independently in foreseeing outcomes of cirrhotic patients. As these parameters lack cost-effectiveness in a rural setup, there is a need for a cost effective and feasible prognostic marker for cirrhotic patients. The present study was aimed at evaluating the role of Absolute Eosinophil Count (AEC) as a prognostic marker in cirrhotic patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated APRI as a very effective noninvasive diagnostic for identifying advanced liver fibrosis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated APRI as a very effective noninvasive diagnostic for identifying advanced liver fibrosis [8,9].…”
Section: Introductionmentioning
confidence: 99%